Perspectives for treating Alzheimer’s disease: a review on promising pharmacological substances - Cazarim, Maurílio de Souza; Moriguti, Julio Cesar; Ogunjimi, Abayomi Tolulope; Pereira, Leonardo Régis Leira (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Dementia is a syndrome characterized by functional and cognitive decline. Alzheimer’s disease (AD) is one of the most common causes of dementia and has high prevalence among the elderly. It is known that there is no drug capable of interfering with the course of the disease. Research on treatments for AD has been marked by the appearance of new drugs and their abandonment. This study aimed to describe drugs that have been studied with regard to treating AD and which are capable of influencing the course of the disease. DESIGN AND SETTING: Narrative review on original articles published worldwide. METHODS: A systematized search was conducted in the PubMed/MEDLINE, Cochrane Library/Cochrane and SciELO/Bireme databases. The descriptors “Molecular Mechanisms of Pharmacological Action” and “Drug Therapy” were each combined with the descriptor “Alzheimer disease”. All of these can be found in MeSH and DeCS. These descriptors were used alone or in combination, and a filter specifying publication between January 2009 and October 2015 in English, Spanish or Portuguese was set. RESULTS: 6,888 articles were found, of which 37 were included in this review; 70.3% of the articles selected were of good quality with low or unclear risk of bias. 86 drugs were considered promising for AD treatment and these were classified into 20 pharmacological categories. CONCLUSION: There are no drugs capable of influencing the course of AD such that treatments are safe and effective. However, immunomodulators stood out as promising, given their effectiveness and quality in the articles analyzed.